ANTITUMOR POTENTIAL OF SEMECARPUS ANACARDIUM AGAINST EHRLICH ASCITES CARCINOMA IN NUDE MICE - S.H. MAJUMDAR, (International Journal of Pharma and Bio Sciences, 2012)
Semecarpus anacardium (SA) popularly known as marking nut has been used in folklore for the treatment of a wide range of diseases. Extracts (hydro-alcoholic and oil) of SA were evaluated for their anticancer activity against Ehrlich ascites carcinoma (EAC) in nude mice. Extracts and standard drug (cyclophosphamide) at a dose of 20 mg/kg body weight were administered orally and continued for 10 consecutive days. The anticancer activity of SA was examined by determining the tumor area, tumor volume and tumor histology in experimental animal models. Both these extracts showed remarkable results in controlling the tumor in EAC bearing nude mice compared to the standard drug cyclophosphamide. Thus, the present study revealed that SA showed anticancer activity in the tested animal models.